2012
DOI: 10.1007/s11832-012-0393-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior spinal fusion in patients with Ehlers–Danlos syndrome: A report of six cases

Abstract: The fragility of the EDS patient population cannot be overlooked. Despite a conservative surgical approach, half of our patients experienced complications. The surgeon choosing to operate on EDS patients must do so with extreme caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
13
1
1
Order By: Relevance
“…All 3 articles emphasized blood loss measurements, which averaged 1272 mL intraoperatively. One reported death postoperatively from vascular compromise was discussed as well [ 24 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 3 articles emphasized blood loss measurements, which averaged 1272 mL intraoperatively. One reported death postoperatively from vascular compromise was discussed as well [ 24 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jasiewicz et al [ 26 ] found that 4 of 11 patients treated for their scoliosis required reoperation secondary to imbalance and instrumentation failure. Rabenhorst et al [ 27 ], looked at 6 patients with Ehlers-Danlos, reported that one patient died following PSF secondary to intra-abdominal bleeding. The authors also noted the need for removal of hardware over one year postoperatively secondary to infection in two patients [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, meticulous hemostasis is needed in these patients [1]. Characteristically, posterior spinal fusion for scoliosis has been associated with excessive bleeding [14,17], leading to death in a patient with postoperative intraabdominal bleeding [17]. Although surgical closure might be complicated by tearing of the skin edges by the sutures, careful multilayered closure with nylon sutures and wound closure strips instead of staples can prevent possible future wound hematoma, wound dehiscence, and resulting infections [21].…”
Section: Discussionmentioning
confidence: 99%
“…Rabenhorst et al [12] сообщили о шести оперированных (средний возраст 14 лет), причем во всех случа-ях диагноз подтвержден результатами генетической экспертизы. Применяли различные варианты дорсального вер-тебрального инструментария, интрао-перационный мониторинг спинного мозга проводили в большинстве слу-чаев.…”
Section: рисunclassified